1982
DOI: 10.1111/j.1365-2141.1982.tb07292.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of myeloperoxidase deficiency in an area of northern Italy: histochemical, biochemical and functional studies

Abstract: Forty-five subjects with a complete deficiency of myeloperoxidase were identified in an area of the region Friuli-Venezia Giulia in north-eastern Italy using the Hemalog D system as the screening technique. Histochemical and biochemical tests performed on the leucocytes of some of these subjects confirmed the defects shown by the Hemalog D system. The defect was of genetic origin in seven subjects. The genetic origin could be suspected in another eight subjects since more than two affected members were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…The enhanced Superoxide anion production (lucigenin chemiluminescence) in myeloperoxidase deficient cells was described in the literature (15,16,23,24), and may be caused by two main reasons: Hasui et al (25) and Stendahl et al· (26) reported an enhanced phagocytosis of myeloperoxidase deficient granulocytes. This report stands in contrast to earlier observations of Cramer et al (27) and Larrocha et al (28), who demonstrated a normal phagocytic behaviour of the myeloperoxidase deficient granulocytes. We could confirm the results that myeloperoxidase deficient granulocytes are able to phagocytose more particles than normal ones (tab.…”
Section: Discussioncontrasting
confidence: 56%
“…The enhanced Superoxide anion production (lucigenin chemiluminescence) in myeloperoxidase deficient cells was described in the literature (15,16,23,24), and may be caused by two main reasons: Hasui et al (25) and Stendahl et al· (26) reported an enhanced phagocytosis of myeloperoxidase deficient granulocytes. This report stands in contrast to earlier observations of Cramer et al (27) and Larrocha et al (28), who demonstrated a normal phagocytic behaviour of the myeloperoxidase deficient granulocytes. We could confirm the results that myeloperoxidase deficient granulocytes are able to phagocytose more particles than normal ones (tab.…”
Section: Discussioncontrasting
confidence: 56%
“…Myeloperoxidase is a constituent of the azurophilic granule and is responsible for the greenish tinge seen in dense neutrophilic infiltrates. As a consequence of the deficient myeloperoxidase, neutrophil killing of some organisms is diminished early but is normal late in killing assays (64). HOCl is a potent microbicidal compound, but H 2 O 2 and granule contents may be primarily responsible for neutrophil killing in standard laboratory assays.…”
Section: Functional Neutrophil Disordersmentioning
confidence: 99%
“…8 MPO deficiency is reported to have an incidence of 1 in 2000-4000 in the United States and Europe and 1 in 55 000 in Japan. [9][10][11][12][13] Candida infections are common in MPO-deficient patients, especially in those that also develop diabetes. 9,[14][15][16][17][18] Occasionally, serious infectious or inflammatory complications have been observed in completely MPOdeficient patients as well.…”
Section: Introductionmentioning
confidence: 99%